2017
DOI: 10.1503/jpn.150247
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain connectivity in patients with schizophrenia is consistent across cognitive contexts

Abstract: IntroductionBeyond abnormal activity of focal brain areas, 1 aberrant functional interactions between brain regions are thought to be a core feature of schizophrenia. [2][3][4] Among the current issues related to this influential idea is whether abnormal functional connectivity in patients with schizophrenia is contextdependent. 5 Resting-state fMRI characterizes intrinsic functional brain connectivity, which is guided by endogenous processes and spontaneous thoughts in the absence of any explicit task. 6 Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…Mass univariate analyses evidenced brain dysconnectivity across the entire brain, with significant effects in over a third of brain connections distributed in various large-scale brain networks, from cognitive to primary sensory networks. Abnormally decreased rather than increased functional connectivity in schizophrenia is largely consistent with previous reports in the literature (Pettersson-Yeo et al, 2011). With close to 200 schizophrenia patients and 200 controls, our fMRI connectome-wide association analysis is one of the largest to be reported to date.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mass univariate analyses evidenced brain dysconnectivity across the entire brain, with significant effects in over a third of brain connections distributed in various large-scale brain networks, from cognitive to primary sensory networks. Abnormally decreased rather than increased functional connectivity in schizophrenia is largely consistent with previous reports in the literature (Pettersson-Yeo et al, 2011). With close to 200 schizophrenia patients and 200 controls, our fMRI connectome-wide association analysis is one of the largest to be reported to date.…”
Section: Discussionsupporting
confidence: 90%
“…Brain imaging data from 6 independent studies were obtained through either the SchizConnect and OpenfMRI data sharing platforms (http://schizconnect.org; https://openfmri.org) or local scanning (Çetin et al, 2014;Gollub et al, 2013;Kogan et al, 2016;Orban et al, 2016;Poldrack et al, 2016;Wang et al, 2016). The 6 datasets differed in terms of both scanning site and cognitive context during fMRI data acquisition (resting-state, emotional memory, Sternberg item recognition paradigm, N-back, task-switching and oddball tasks).…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies applying this strategy in ASD have shown reproducible patterns of both over-connectivity (prefrontal and parietal cortices) and under-connectivity (sensory-motor regions) 19 . In contrast, SZ patients tend to exhibit a general under-connectivity profile, mainly involving the medial prefrontal cortex, the cingulate and the temporal lobe 20 , with the exception of over-connectivity of the thalamus 21 . These altered networks do not appear to be disorder-specific and have been reported across several disorders, including ASD, ADHD, and SZ 22 .…”
Section: Introductionmentioning
confidence: 91%
“…Decreased connectivity with the PFC is further correlated with restrictive and repetitive behaviors, a keystone phenotype in the diagnosis of ASD (Delbruck et al, 2019). PFC functionality deficits are prevalent in schizophrenia as well, with both hypoactivation phenotypes (Huang et al, 2010;Denardo et al, 2015) and consistent reduced connectivity reported (Woodward et al, 2012;Orban et al, 2017;Giraldo-Chica et al, 2018;Chen et al, 2019;Bulletin et al, 2020). Although additional experiments are necessary to investigate intrahemispheric connectivity disruptions in the Cited2 cKO, including those to the PFC, it is likely that disruptions in both long-distance intrahemispheric and interhemispheric connectivity contribute to the behavioral disruptions in the Cited2 cKO.…”
Section: Discussionmentioning
confidence: 99%